Clinical and Translational Medicine - Abraham, Edward; Chen, Zhinan; Marincola, Francesco M.; Wang, Xiangdong; Zerhouni, Elias; Wang, Xiangdong
Clinical and Translational Medicine aims to play an important and recognized role in reporting knowledge that contributes towards the understanding of molecular mechanisms of disease. The journal also aims to foster a predictive, preventive, personalized and practical approach towards precision medicine, leading to improved patient prognosis. The journal provides a forum for the exchange of ideas between basic and clinical scientists on molecular and cellular mechanisms of disease and potential therapies. The journal covers all areas of clinical and translational medicine but also has several specialised sections: Clinical and translational cardiovascular medicine - Edited by Yong-Xiao Wang Clinical biostatistics – Edited by Christian Baumgartner and Xiangdong Wang Clinical genomics - Edited by Olaf A. Bodamer and Gilbert S. Omenn Stem cell therapies - Edited by Mariusz Z. Ratajczak Translational respiratory medicine - Edited by Chunxue Bai Vaccination and immunotherapy – Edited by Marek Malecki  Clinical and Translational Medicine is a truly international, peer-reviewed, and open access journal devoted to the publication of articles on scientific and clinical investigations which will promote and accelerate the translation of preclinical research to a clinical application and the communication between basic and clinical scientists. The journal emphasizes clinical potential and application of new biotechnologies, biomaterials, bioengineering, disease-specific biomarkers, cellular and molecular medicine, omics science, bioinformatics, applied immunology, molecular imaging, drug discovery and development, and regulation and health policy. The journal will specially focus on the bench to bedside approach, favouring studies and clinical observations which generate hypotheses and questions relevant to the patient and disease and guide the investigations of cellular and molecular medicine. Clinical and Translational Medicine welcomes submissions from companies, clinicians, scientists and policy makers.